The Use of Singlish Discourse Particle ‘Lah’ in Sgag’s Videos - Febryanto, Ryan; Suastra, I Made (Humanis, 2018)
This study entitled The Use of Singlish Discourse Particle ‘lah’ in SGAG’s Videos is aimed to analyze the types and function of discourse particle in SGAG’s videos. The data were taken from the conversation in SGAG’s video collection. Descriptive qualitative method was applied to analyze the types and functions of discourse particle ‘lah’. The theories used to analyze it are the classification of the type of discourse particle theory by Wong, role of particles theory by Ling and Deterding and Context of Situation by Halliday. The result of analysis shows that there were 62 discourse particle lah in the SGAG’s video collection from May 28 th 2017 until October 10 th 2017. The major type of discourse particle lah was Propositional lah (33 occurrences) and the function is more often as a pragmatic role (56 occurrences) rather than a syntactic function (6 occurrences).